Morphological and molecular characterization of Buzionema lutgardae n. sp. (Nematoda: Oxyuridomorpha: Thelastomatidae) from the cockroach Byrsotria sp. (Blattaria: Blaberidae) in Cuba - Morffe, Jans; García, Nayla; Hasegawa, Koichi; Carreno, Ramon A. (Zootaxa, 2021)
Buzionema lutgardae n. sp. (Nematoda: Oxyuridomorpha: Thelastomatidae) is described from the cockroach Byrsotria sp. (Blattaria: Blaberidae), endemic to Cuba. Females of B. lutgardae n. sp. are shorter than those of B. validum Kloss, 1966 (1600–2150 µm vs. 3131–3378 µm), but the oesophagus is comparatively longer (b = 2.96–3.77 vs. 4.65–4.87). The lateral alae of the new species extend from ca. the midpoint of the cylindrical part of the procorpus to the level of the anus in contrast to the base of the basal bulb to the level of the anus in B. validum. The males of B. lutgardae n. sp. are shorter than those of B. validum (780–940 µm vs. 1177–1423 µm) and their lateral alae end at some distance before the cloaca instead the level of the cloaca in B. validum. The phylogeny of B. lutgardae n. sp. is inferred by the D2-D3 domains of the 28S rDNA. B. lutgardae n. sp. and B. validum form a monophyletic clade with strong nodal support, as sister-group of the genus Leidynema Schwenck in Travassos, 1929.